Analysis of the Impact of Indomaret's Presence on SME Income in Ambon City (Case Study on SME Traders in Urimessing Village, RT 009/RW 003, Siwang Village - Louhattu, Octovina Sonya; Sahusilawane, Stevie; Louhenapessy, William George (JENDELA PENGETAHUAN, 2023)
Income is all receipts in the form of money or goods originating from other parties or industrial products valued for the services of an amount of money from assets that are in effect at that time. Income is a person's source of income to meet daily needs and is very important for the survival and livelihood of a person, directly or indirectly. Likewise, with SME traders in Urimessing Village, the income of traders has begun to decline. This study uses a population of 30 samples and five quantitative research methods. After the presence of Indomaret in Ambon City, SME income began to decline because many consumers preferred shopping at Indomaret rather than at SMEs and using a simple pre-test. Anova 75222.339, Model summary 435.965, Report 629.85, Paired samples test 000.33.